Global livestock development: Policies and vision - SHRIKANT BHIMRAO KHADE; R S KHILLARE; M B DASTAGIRI (Indian Journal of Animal Sciences, 2021)
Owing to the anthropogenic pressures, the global food system is undergoing significant changes. Due to increasing human population forecasted, more than 9 billion by 2050, there is an increase in the food demand and consumption by whole population. The world as a whole is undergoing several transformative changes. Growing population, changing lifestyles, expanding urbanization and accelerated climate changes are forming novel challenges for the global livestock system. Day-by-day due to continuous changes in food consumption patterns, i.e. increased demand for cattle products, resulting from urbanisation, rising affluence, and nutritional and environmental concerns are influencing what we eat, who consumes it, and how much we eat more than ever before. The dual burdens of nutrition, i.e. either overconsumption or malnutrition, along with the need to alleviate the climate change effects, are shaping research priorities, influencing policy, and changing people’s perceptions of food in different ways. The livestock industry is a fast-paced industry. It is changing in developing nations as a result of the rapidly increasing demand for animal products. Demand for cattle products is stagnant in industrialised countries, while many production techniques are improving their efficiency and environmental sustainability. Human population expansion, wealth growth, and urbanisation have all influenced demand for products of livestock in the past, and the production response in various livestock systems has been linked to science and technology and rises in animal population. Rivalry for natural resources, notably land and water, as well as competition between food and feed, will progressively effect output in the future. Recognition of United Nations (UN) 2030 Agenda for Sustainable Development as a broad framework that directs growth of the global livestock sector.